Assessment Strategy to Rectify EFL Students’ Performance: A Need Analysis - Maruf, Nirwanto; Helingo, Adimawati (JET ADI BUANA, 2022)
The objective of this research is to investigates the assessment strategies that required to be implemented, and are favorable for the learners in order to rectify EFL students’ performance regards to their language performance. This study conducted based on the presumption that teachers merely consider students’ preference on how they want to be assessed. A need analysis is administered to meet the objective of the research. The result indicates that learners mostly prefer to have corrective feedback from the teacher during the teaching and learning activities, meanwhile performance task and quiz assessment are preferred by learners as their assessment strategies instead of summative assessment. Nevertheless in spite of that, KWL assessment strategy is also recommended for the teaching and learning of English.